Dual Responsive Poly(N‐vinylcaprolactam) Based Degradable Microgels for Drug Delivery. (11th October 2017) - Agrawal, Garima; Agrawal, Rahul; Pich, Andrij
Abstract: Poly( N ‐vinylcaprolactam)‐based biodegradable microgels are prepared for drug delivery application via precipitation polymerization using diacetone acrylamide (DAAM) and dimethyl itaconate (IADME) as comonomers. The microgel particles are subsequently crosslinked by addition of adipic acid dihydrazide, which reacts with the ketone groups of DAAM. Itaconic acid (IA) groups are generated by the hydrolysis of IADME units inside the microgels resulting into both pH and temperature sensitive microgel particles. Volume phase transition temperature of the obtained microgels is influenced by both IA content and pH of the surrounding medium. Due to the incorporation of hydrazone linkages, the microgels show degradation under acidic conditions. These microgels can effectively encapsulate doxorubicin (DOX) as a model drug and show low DOX leakage under physiological conditions while rapid DOX release is observed at low pH. The results of the cytotoxicity assay further display that the DOX‐loaded microgels exhibit effective antitumor activity against HeLa cells demonstrating their great potential as drug delivery carriers for cancer therapy. Abstract : Poly( N ‐vinylcaprolactam) based dual responsive microgels show degradation under acidic conditions due to the incorporation of hydrazone linkages. These microgels can effectively encapsulate doxorubicin (DOX) as a model drug and show low DOX leakage under physiological conditions but rapid DOX release at low pH. DOX‐loaded microgels exhibit effective antitumor activity against cancer cells demonstrating their great potential for cancer therapy.